ANDROID GAME FOR TYPING SKILL EVALUATION - Imansyah, Pranadya Bagus; Wibawa, Aji Prasetya; Widiyaningtyas, Triyanna (Universitas Negeri Malang, 2018)
As social beings, humans basically need does communication to express his wishes. As the technological progress, the developers are competing to create applications that facilitate communication relationships in both personal and group. In use, it is often found that a classic problem called ?typo? that has led to the misunderstanding in socializing. With the development of game applications based on Android, it will generate data in the form of feasibility and development typing ability of before, after, even when usage by counting the number of letters that can be solved also see the speed of words per minute users that aims to train the speed and accuracy of the type which may be impact on the ability to type in a user's social media.